2017
DOI: 10.1002/chem.201605782
|View full text |Cite
|
Sign up to set email alerts
|

Optical Sensing of Anions via Supramolecular Recognition with Biimidazole Complexes

Abstract: Phosphorescent metal complexes with peripheral N-H donor functionalities have attracted great attention as potential molecular sensing units for anionic species lately. In this contribution we discuss the development and potential of anion recognition and sensing features of recent examples of luminescent 2,2'-biimidazole complexes of ruthenium(II), iridium(III), osmium(II) and cobalt(III). The general dependency of photophysical features in these complexes regarding the acid-base chemistry of the peripheral N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 98 publications
(182 reference statements)
0
27
0
Order By: Relevance
“…Although Ru II complexes are potent sensing units featuring highly beneficial charge assistance of XBs, [13b, c, 20b] their twofold cationic charge may induce solubility issues as well as unspecific electrostatic interactions to reach charge neutrality in organic solvent mixtures. Hence, the structurally related but monocationic congener [Ir(bpy)(ppy) 2 ] + (ppy=phenylpyridine) is an attractive alternative [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Although Ru II complexes are potent sensing units featuring highly beneficial charge assistance of XBs, [13b, c, 20b] their twofold cationic charge may induce solubility issues as well as unspecific electrostatic interactions to reach charge neutrality in organic solvent mixtures. Hence, the structurally related but monocationic congener [Ir(bpy)(ppy) 2 ] + (ppy=phenylpyridine) is an attractive alternative [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the simple mix‐&‐read test‐strip assay demonstrated that this approach is very appealing for powerful and reliable analytics for everyday life in a relevant concentration range. If one considers that over the past four decades a vast number of small‐molecule probes for a large number of analytes have been reported in the literature, of which, however, only a few operate in neat aqueous solution, reconsideration of one or the other probe molecules and combination with suitably tailored nanomaterials in view of our present work might lead in a rather straightforward manner to various other potent indicator materials for comparatively simple analytical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The binding interaction is authenticated from single-crystal X-ray structure of new Mo(VI) complex (M1). The sequential detection limits for AsO 2 – and H 2 PO 4 – are 1.2 × 10 –10 and 3.2 × 10 –6 M, respectively, whereas the corresponding binding constants are 6.49 × 10 4 and 2.11 × 10 5 M –1 .…”
Section: Introductionmentioning
confidence: 96%